Letters : High-coupling distributed feedback lasers for the 1.55 μm spectral region. (19th September 2019) - Dudelev, V V; Mikhailov, D A; Chistyakov, D V; Kognovitskaya, E A; Lyutetskiy, A V; Slipchenko, S O; Pikhtin, N A; Gladyshev, A G; Denisov, D V; Voropaev, K O; Ionov, A S; Babichev, A V; et al.
Abstract: A technique for the development of high-coupling distributed-feedback (DFB) lasers for the 1.55 μm spectral region is described. The lasers demonstrate stable single-frequency generation in a broad temperature range with a maximum side-mode suppression ratio of more than 30 dB.